Bioequivalence Studies Of Vitamin Gummies And Vitamin Supplements (International Journal of Food and Nutritional Sciences, 2023)
Vitamin supplements are incredibly popular all over the world. Many people believe that taking vitamins can improve health or make up for a diet that’s low in nutrients. There are several types of vitamins, including chewable gummies. They may include several vitamins and minerals or just a few select nutrients, such as vitamin D and calcium.